Core and activating Symptoms of Depression in Chinese Teachers and Comparison between Different Gender and Stage of Teaching: A Network Analysis Approach - Shumeng Ma; Ning Jia; Jinghua Dai (Journal of Behavior Therapy And Mental Health, 2026)
Background Depression, increasingly recognized as a critical factor impacting mental health, notably affects various populations, including teachers. This study aimed to delineate the specific characteristics of depressive symptom networks among Chinese teachers, identify the core symptoms of depression within this demographic, and examine the variations in depressive symptom networks across different genders and teaching stages. Method The study encompassed 1,670 teachers. Depressive symptoms were assessed using the Self-Rating Depression Scale (SDS). Central symptoms were identified through centrality indices. Network stability was examined via a case-dropping procedure. Directed Acyclic Graphs (DAG) was used to identify the activating symptoms. Results “Personal devaluation” exhibited the highest and most stable centrality values in the network. “Depressed Affect” and “Emptiness of Life” were identified as the activating symptoms in the network. No significant differences were observed in the network structure and global strength of depression between teachers of different genders. However, significant differences in the network’s global strength were found between junior and senior high school teachers. Conclusion “Personal devaluation” emerged as the core depressive symptoms among teachers in China. “Depressed Affect” and “Emptiness of Life” serve as the gateways that activate the entire teacher depression network. Paying close attention to these symptoms could potentially alleviate the experiences of depression in this demographic.
Keywords: Depression